Potential regularization as the method accounting for short-range correlations in the electron liquid theory - Vavrukh, M.V.; Tyshko, N.L. (Condensed Matter Physics, 2004)
In our previous paper [1] we proposed a Coulomb potential regularization as one of the methods for short-range correlation accounting in the electron liquid model. The present paper formulates the criterions of optimal choice of regularization as well as calculates the energetic, structural and dielectric characteristics of the model.